A configural model of expert judgement as a preliminary epidemiological study of injury problems: An application to drowning - Morgan, Damian (PLoS One, 2019)
Robust epidemiological studies identifying determinants of negative health outcomes require significant research effort. Expert judgement is proposed as an efficient alternative or preliminary research design for risk factor identification associated with unintentional injury. This proposition was tested in a multi-factorial balanced experimental design using specialist judges (N = 18), lifeguards and surfers, to assess the risk contribution to drowning for swimming ability, surf bathing experience, and wave height. All factors provided unique contributions to drowning risk (p < .001). An interaction (p = .02) indicated that occasional surf bathers face a proportionally increased risk of drowning at increased wave heights relative to experienced surf bathers. Although findings were limited by strict criteria, and no gold standard comparison data were available, the study provides new evidence on causal risk factors for a drowning scenario. Countermeasures based on these factors are proposed. Further application of the method may assist in developing new interventions to reduce unintentional injury.